Analysis of Indonesian Sharia Bank Marketing Strategy in Facing Financial Industry Competition - Wanda Eflinda Aryanti; Muhammad Iqbal Fhase (Research of Scientia Naturalis, 2024)
Marketing is an activity of all deparments in a company or bank. A holistic marketing philosophy that recognizes that anything can happen in marketing. Therefore, marketing must be managed systematically so that marketing objectives can be achieved in accordance with marketing objectives. company objectives. The banking industry is a service industry and cannot be separated from the daily activities of society. This study aims to understand the marketing strategy implemented by Islamic banks in facing industrial competition. This study was conducted using a qualitative descriptive method. The results of this study indicate that Islamic banks have the ability to compete in a very competitive market by strengthening cooperation with cooperatives to build better relationships with entrepreneurs and the government, increasing customer loyalty, improving product quality, and increasing promotional effects by using various media . and developing effective and efficient marketing strategies.